Sosialisasi Terapi Menulis Ekspresif Sebagai Pendekatan Self-Healing untuk Meningkatkan Kesehatan Mental Mahasiswa - Siska Putri Belangi (Lembaga Pengembangan Kinerja Dosen, 2024)
Self-healing refers to a process of treatment or healing that is carried out by oneself through a process of self-confidence and is also supported by a supportive environment and external factors. The implementation of the activity